SELF-CONTROL IN JODI PICOULT SMALL GREAT THINGS - Pingkan Windy Runtukahu; Olga A. Rorintulus; Delli Sabudu (Program Studi Pendidikan Bahasa Inggris, 2022)
To revealed the self-control of Ruth Jefferson in Jodi Picoult’s Small Great Things. This research was qualitative research which is represented in the form of words. The data source in this research was a novel of Small Great things by Jodi Picoult. In analysing the data the writer used psychological approach from Sigmund Freud who states that each individual’s personality is made of three parts: The Ego, the Superego and the Id. In this study there are various findings that not only contribute to the research that is currently being made, but also provide many lessons for every human being, especially our social life which sometimes has a relationship with the problems in the Small Great Things novel. As raised in this study, namely Self-control which is reflected in the main character in this novel, namely Ruth Jefferson, how is Ruth's attitude and psychology in dealing with every problem, be it accusations, discrimination, humiliation and even the legal process that ensnares her which is not actually her. the mistake. There are 6 things related to self-control which are reflected in Ruth Jefferson's attitude, namely: Being Indulgent, High Self-esteem, Personal Qualities, High Self-Defense, Overcome, Low-Profile. Through these findings, it can be concluded that the inner emotional strength is a benchmark for how strong Ruth Jefferson's self-control is in Self-control in Jodi Picoult's novel Small Great Things